The Effect of Music-Based Warm-Up Exercises on Student Active Participation in Physical Education at Public Senior High School 16 Bandung - Elvira Nulhakim; Asep Sumpena; Agus Gumilar (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of music-based warm-up modifications on students' active participation in Physical Education learning at Public Senior High School 16 Bandung. Music-based warm-up was chosen because music has been proven to improve mood, foster enthusiasm, and reduce student boredom. The background of the study stems from the problem of low student participation in Physical Education learning due to monotonous and less varied teaching methods. This study used an experimental method with a one-group pretest-posttest design. The research sample was 204 grade XII students selected using a simple random sampling technique. The research instrument was a student active participation questionnaire compiled based on Keith Davis's theory, supplemented by observation and documentation sheets. Data were analyzed using the Wilcoxon Signed Rank Test through SPSS 16.0 for Windows. The results showed a significant difference between the pretest and posttest scores, where the majority of students experienced an increase in active participation after being given music-based warm-up treatment. These findings indicate that music-based warm-up can create a pleasant learning atmosphere, meet students' psychological needs, and increase their intrinsic motivation. Thus, this innovative learning strategy can be an effective alternative to improve the quality of PE learning in secondary schools and encourage more optimal student involvement.